Potential of green solvent as a polyphenolic and antioxidant extraction medium in brown seaweed sargassum cristaefolium - Syarifah, Laili -; Yuliana, Elsa; Novitasari, Jihan; Pamungkas, Pinctada Putri; Khurniyati, Maylina Ilhami; Rohim, Abd. (Jurnal Teknologi Pangan, 2026)
This study aimed to evaluate the effectiveness of environmentally friendly water based solvents in extracting polyphenolic compounds and determining the antioxidant activity of the brown seaweed Sargassum cristaefolium. The research employed a quantitative experimental approach using different types of water solvents, namely distilled water, municipal tap water, and commercial mineral water. The extraction process was carried out at temperatures of 40°C, 55°C, and 70°C with extraction times of 20, 40, and 60 minutes. Parameters analyzed included total phenolic content, total flavonoid content, and antioxidant activity measured using the DPPH method. The results showed that solvent type and extraction conditions significantly influenced the release of bioactive compounds. The highest antioxidant activity of 79.40 percent was obtained using mineral water at 40°C for 60 minutes. The highest total phenolic content was observed in commercial mineral water at 70°C with a value of 2.42 mg GAE per g, while the highest flavonoid content was obtained using distilled water at 70°C for 60 minutes reaching 4595.42 µg QE per g. Increasing extraction temperature and time generally enhanced polyphenol and flavonoid levels until a certain limit before thermal degradation occurred. Minerals in mineral water improved stability and solubility of bioactive compounds during extraction processes overall